Interdisciplinary perspectives on multimorbidity in Africa: Developing an expanded conceptual model. - Justin Dixon; Ben Morton; Misheck J Nkhata; Alan Silman; Ibrahim G Simiyu; Stephen A Spencer; Myrna Van Pinxteren; Christopher Bunn; Claire Calderwood; Clare I R Chandler; Edith Chikumbu; Amelia C Crampin; et al. (Public Library of Science (PLoS), 2024)
Multimorbidity is an emerging challenge for health systems globally. It is commonly defined as the co-occurrence of two or more chronic conditions in one person, but its meaning remains a lively area of academic debate, and the utility of the concept beyond high-income settings is uncertain. This article presents the findings from an interdisciplinary research initiative that drew together 60 academic and applied partners working in 10 African countries to answer the questions: how useful is the concept of multimorbidity within Africa? Can the concept be adapted to context to optimise its transformative potentials? During a three-day concept-building workshop, we investigated how the definition of multimorbidity was understood across diverse disciplinary and regional perspectives, evaluated the utility and limitations of existing concepts and definitions, and considered how to build a more context-sensitive, cross-cutting description of multimorbidity. This iterative process was guided by the principles of grounded theory and involved focus- and whole-group discussions during the workshop, thematic coding of workshop discussions, and further post-workshop development and refinement. Three thematic domains emerged from workshop discussions: the current focus of multimorbidity on constituent diseases; the potential for revised concepts to centre the priorities, needs, and social context of people living with multimorbidity (PLWMM); and the need for revised concepts to respond to varied conceptual priorities amongst stakeholders. These themes fed into the development of an expanded conceptual model that centres the catastrophic impacts multimorbidity can have for PLWMM, families and support structures, service providers, and health systems.